Relationship between menopausal status, fat intake, and fiber intake with women cholesterol level - Heldi, Ilza Wahyuni; Dewi, Mira; Briawan, Dodik (Alma Ata University Press, 2025)
ABSTRAK Latar Belakang : Kadar kolesterol yang tinggi merupakan faktor risiko penyakit kardiovaskular. Kadar kolesterol yang tinggi disebabkan oleh berbagai faktor antara lain asupan lemak dan status menopause. Wanita menopause rentan mengalami kadar kolesterol tinggi karena pada wanita pascamenopause terjadi penurunan produksi hormon estrogen yang berfungsi mengatur metabolisme lipid. Asupan lemak yang tinggi mempengaruhi kadar kolesterol. Namun mengonsumsi asupan serat yang cukup dapat mengontrol kadar kolesterol agar tetap stabil. Banyak penelitian telah dilakukan mengenai hubungan antara asupan lemak dan serat dengan kadar kolesterol. Namun, hanya sedikit yang melakukan penelitian pada wanita, terutama mengenai status menopause. Tujuan : Tujuan penelitian ini adalah untuk mengetahui apakah terdapat hubungan antara status menopause, asupan lemak, dan asupan serat dengan kadar kolesterol wanita di indonesia.Metode : Desain penelitian ini adalah cross sectional dengan subjek perempuan berusia 15-54 tahun di 10 provinsi di Indonesia. Kadar kolesterol darah diperoleh dari pengukuran darah kapiler dan asupan lemak dan serat diperoleh dari wawancara dengan metode SQ-FFQ yang dilakukan oleh tenaga kesehatan terampil. Status menopause diperoleh dari wawancara yang dilakukan oleh enumerator terlatih yang menanyakan riwayat menstruasi dalam satu tahun. Klasifikasi status menopause dibedakan menjadi belum menopause, pra menopause, dan pasca menopause. Hasil : Dari total 606 subjek, 122 subjek mempunyai kadar kolesterol tinggi. Terdapat hubungan yang signifikan antara status menopause dengan kadar kolesterol (p<0,05) dengan tingkat korelasi r=0,013. Dan tidak terdapat hubungan yang bermakna antara asupan lemak dan asupan serat dengan kadar kolesterol (p>0,05) dengan tingkat korelasi masing-masing r=0,060 dan r=0,297.Kesimpulan : Status menopause mempunyai pengaruh yang signifikan terhadap kadar kolesterol. KATA KUNCI : asupan lemak; asupan serat; kadar kolesterol; status menopause; wanita ABSTRACT Background : High cholesterol levels are a risk factor for cardiovascular disease. High cholesterol levels are caused by various factors including fat intake and menopausal status. Menopausal women are susceptible to high cholesterol levels because in postmenopausal women there is a decrease in the production of the hormone estrogen which functions to regulate lipid metabolism. High fat intake affects cholesterol levels. However, consuming sufficient fiber intake can control cholesterol levels so that they remain stable. Many studies have been conducted on the relationship between fat and fiber intake and cholesterol levels. But, only a few have studied in women, especially regarding menopausal status.Objectives : The aim of this study was to determine whether there is a relationship between menopausal status, fat intake and fiber intake with cholesterol levels in Indonesian women.Methode : The design of this study was cross sectional with female subjects aged 15-54 years in 10 provinces in Indonesia. Subject selection will be carried out using purposive sampling methode. Blood cholesterol levels were obtained from capillary blood measurements and fat and fiber intake were obtained from interviews using SQ-FFQ method conducted by skilled health workers. Menopausal status was obtained from interviews conducted by trained enumerators who asked about menstrual history within one year. The classification of menopausal status is divided into not yet menopausal, pre-menopausal, and post-menopausal.Result : Of the total 606 subjects, 20,1% subjects had high cholesterol levels. The average fat intake of the subjects was 47.5 g or 75%. The average fiber intake of the subjects was 12.5 g or 42.6%. There is a significant relationship between menopausal status and cholesterol levels (p<0.05) with a correlation level of r=0.013. And there was no significant relationship between fat intake and fiber intake and cholesterol levels (p>0.05) with correlation levels of r=0.060 and r=0.297 respectively.Conclution : Menopausal status has a significant effect on cholesterol levels. KEY WORDS: cholesterol level; fat intake; fiber intake; menopausal status; women Received: 06 Jan 2025; Revised: 26 July 2024; Accepted: 26 Jan 2025; Available online: 30 Mar 2025; Published: 30 Mar 2025